Nuclear Power: Finding the missing piece - Mirza, Mateen (Cranfield University, 2022)
There is now a clear consensus that our energy demands must be met through lower carbon solutions. As our global population continues to rise and aspires to higher living standards we are faced with increasingly ambitious energy targets in the transport, industry and power sectors. Nuclear power remains one of the few reliable energy sources. However, there remains a missing piece to the puzzle. Whether this relates to spent nuclear fuel reprocessing, the ongoing issue of waste disposal or improving our fleet of nuclear reactor systems is left to the viewer's thoughts.
Keywords: DSDS2022 Digital Image; DSDS2022; Nuclear power; Energy